MANUFACTURE OF CONDUCTIVE FABRIC COATED SILVER NANOPARTICLES AND POLYANILINE AS FLEXIBLE ELECTRODE FOR ELECTROMIGRAPHIC MEASUREMENT (EMG) - Ghifari Nurlis, Aulia
Flexible electrodes with high electrical conductivity, good contact, safety, and comfortable characteristics are desirable for measurement of long duration biopotential signals. The use of textile materials in the form of cotton fabric as a basic substrate with the addition of silver nanoparticles (AgNP) and polyaniline (PANI) was developed as a flexible electrode for measuring muscle biopotential signals using electromyography (EMG) in this study. AgNP was synthesized using various reducing agents and solution pH. Variations of reducing agents used are Gum Acacia and Hydrazine Hydrate. AgNP synthesis process is also varied when the pH is acidic, neutral, and basic. The effect of sample variation will be studied by measuring the electrical conductivity of each sample and also by comparing the performance of flexible electrodes during EMG measurements. The results obtained from this study are the AgNP PANI electrodes synthesized using Gum Acacia at alkaline pH have very high SNR and conductivity. In addition, the absence of an electrolyte gel during EMG measurements using flexible electrodes has been developed to provide comfort to the user without the risk of skin irritation due to the electrolyte gel when the measurement process is carried out for a long time. Therefore, the AgNP PANI cloth electrode synthesized with Gum Acacia as a reducing agent at alkaline pH is expected to be used as a substitute for commercial electrodes in the future.